FERROMAGNETIC NANOTUBES IN PORES OF TRACK MEMBRANES FOR THE FLEXIBLE ELECTRONIC ELEMENTS - E. Yu. Kaniukov; E. E. Shumskaya; M. D. Kutuzau; D. B. Borgekov; I. E. Kenzhina; A. L. Kozlovskiy; M. V. Zdorovets (Приборы и методы измерений)
In the paper the template synthesis of ferromagnetic (Fe, Co, Ni) nanotubes in the pores of track membranes were studied. The aim of this work was determination of nanotubes basic structural and magnetic parameters and demonstration of the possibility of application in the flexible electronics elements.By electrochemical deposition, ferromagnetic nanotubes with a diameter of 110 nm and an aspect ratio of 100 were formed in the pores of polyethylene terephthalate track membranes. The morphology of the obtained nanostructures were studied by scanning electron microscopy, the elemental composition was determined by the energy-dispersion analysis. Using the X-ray structural analysis, the main parameters of the crystal structure were established: lattice type, lattice parameter and average crystallite size. The magnetic properties were studied by the method of vibrational magnetometry.It was shown that in the selected conditions of synthesis without reference to the type of ferromagnetic metals nanotubes had the same dimensions – length, diameter and wall thickness. The produced nanotubes consisted of iron, cobalt and nickel, respectively without oxides impurities. Nanotubes had a polycrystalline structure of walls with a body-centered cubic (iron), face-centered cubic (cobalt and nickel) crystal lattice. According to the main magnetic parameters, nanotubes belonged to a group of soft magnetic materials. Also, the presence of magnetic anisotropy, which is caused by the features of crystalline structure and shape of the nanostructures.Based on the analysis of structural and magnetic characteristics of ferromagnetic nanotubes which were synthesized in the pores of track membranes, were proposed the main principles of their using in the elements’ of flexible electronics constructing (magnetic field direction sensors and magnetic memory elements).